Highly Fluorescent, Photostable, Conjugated Polymer Dots with Amorphous, Glassy‐State, Coarsened Structure for Bioimaging. Issue 1 (25th September 2014) - Kim, Beomsu Shin‐Il; Jin, Young‐Jae; Lee, Wang‐Eun; Byun, Doo Jin; Yu, Ri; Park, Sang‐Joon; Kim, Hyojin; Song, Kyu‐Ho; Jang, Sung‐Yeon; Kwak, Giseop
<x xml:space="preserve">Abstract</x> In this paper, specific molecular design rules are proposed for highly fluorescent, photostable, conjugated polymer dots (CPDs) applicable for the bioimaging of live cells. CPDs are prepared by nanoprecipitation in water using polydiphenylacetylene (PDPA) derivatives and commercial conjugated polymers. Among these, an amorphous, glassy‐state PDPA derivative provides highly porous, coarsened nanoparticles. The nanoparticles are dispersed very well in water, and the polymer chains are either hydrodynamically or thermodynamically stable, with a fully relaxed intramolecular stacked structure. This leads to effective radiative emission decays by restraining collisional quenching and vibrational relaxation to achieve an extremely high fluorescence (FL) quantum efficiency. The FL emission quantum yield is as high as 0.76, which is the highest value among those reported for conventional CPDs. The PDPA‐based CPD has a very low photobleaching quantum yield (∼10−9), because of its relatively high ionization potential. This aqueous colloidal solution is useful for bioimaging plant and mammalian cells. The excellent FL quantum efficiency, photostability, and cellular uptake suggest that the present CPD is a very promising probe for bioimaging, particularly for long‐term imaging and tracking in live cells or experimental animals.